The visual culture and the classics: an interview with Jaś Elsner - Elsner, Jaś; Pina, Edjalma Nepomoceno (Romanitas - Revista de Estudos Grecolatinos, 2024)
Interview with Jaś Elsner.
Keywords: Jaś Elsner; Visual culture; Classics